Pengaruh Dewan Komisaris, Dewan Direksi, Dan Komite Audit Terhadap Kinerja Keuangan Perusahaan Dengan Kualitas Audit Sebagai Variabel Moderasi - Sri Handayani; Sofyan Helmi Purba (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. This study aims to reveal the influence of the board of commissioners, board of directors, and audit committee on financial performance, with audit quality as a moderating variable. This research uses a quantitative method. The population in this study consists of energi sector companies listed on the Indonesia Stock Exchange during 2021–2024. The sampling technique is based on purposive sampling. From a population of 90 companies in the energi sector listed on the Indonesia Stock Exchange, applying the sample selection criteria resulted in 10 companies, producing a total of 40 observations. The statistical tool used in this study is EViews 12, and the analysis technique applied is panel data regression.The results of this study indicate that, simultaneously, the board of commissioners, board of directors, and audit committee have an effect on financial performance. Partial testing shows that the board of commissioners does not affect financial performance, the board of directors does not affect financial performance, while the audit committee does affect financial performance. Furthermore, the results of the moderating regression analysis (MRA) show that audit quality does not moderate the relationship between the board of commissioners and financial performance, but audit quality does moderate the relationship between the board of directors and financial performance, as well as the relationship between the audit committee and financial performance.